Don't just say what you mean - Contextualize it: A leadership study across 17 countries - (:unkn) unknown (My University, 2009)
With the increasing adoption of English by corporations, the issue of language management in multilingual organizations and the pros and cons of standardization have been debated in the literature. Our study considers whether the language issue is as important as much of the literature suggests, and questions whether it is the root cause of difficulties in communication, interpretations of and reactions to management situations. We posit that more attention should be given to situational and contextual factors, and empirically test and compare the effects of language and other factors, on both workplace attitudes and reactions to specific leadership scenario-based situations across 17 countries. We find that nationality and personal characteristics shape one's way of thinking, interpretations and preferences more than the language imposed upon individuals.
Keywords: Culture; Language; Leadership